THE BASIC PRINCIPLES OF EMPIRICISM IN LITERARY THEORY AND CRITICISM: Sources and contemporary empirical researches - Anisimova, Liudmyla V. (Синопсис: текст, контекст, медіа, 2013)
The article deals with the research of the basic principles of empiricism in Reader-response theory within the environment of American and European literary criticism, beginning with I.A. Richards as its important precursor and ending with contemporary empirical researchers (W. van Peer, D.S. Miall & D. Kuiken) as its indirect successors. Key words: empiricism, Reader-response theory, empirical researches